Engineering microbial hosts for production of bacterial natural products. Issue 8 (13th April 2016) - Zhang, Mingzi M.; Wang, Yajie; Ang, Ee Lui; Zhao, Huimin
Abstract : Microbial fermentation provides an attractive alternative to chemical synthesis for the production of structurally complex natural products. Abstract : Covering up to end 2015 Microbial fermentation provides an attractive alternative to chemical synthesis for the production of structurally complex natural products. In most cases, however, production titers are low and need to be improved for compound characterization and/or commercial production. Owing to advances in functional genomics and genetic engineering technologies, microbial hosts can be engineered to overproduce a desired natural product, greatly accelerating the traditionally time-consuming strain improvement process. This review covers recent developments and challenges in the engineering of native and heterologous microbial hosts for the production of bacterial natural products, focusing on the genetic tools and strategies for strain improvement. Special emphasis is placed on bioactive secondary metabolites from actinomycetes. The considerations for the choice of host systems will also be discussed in this review.